تحليل التجارة الخارجية في سورية (2005-2009) - محمود, حبيب (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث العديد من النقاط البحثية وهي أهم نظريات تحرير التجارة الخارجية (حيث سنحلل الموقف الأكاديمي العالمي من عملية تحرير التجارة وأثرها النظري)، ثم ننتقل إلى تحليل اتفاقيات تحرير التجارة السورية- العالمية (مع الدول العربية، تركية والاتحاد الأوربي)، ورصد مدى استفادة سورية منها، بعد ذلك نحلل التجارة الخارجية السورية عبر مؤشرات التجارة الخارجية لنصل إلى تقديم صورة عن الأهمية الاقتصادية للتجارة الخارجية في الفترة المرصودة، لنخلص إلى جملة من التوصيات والمقترحات. The research deals with many points that are the most important theories of liberalization of foreign trade (where we will analyze the academic world situation of the process of trade liberalization and its theoretical impact), and then we move on to the analysis of Syrian - Global trade liberalization agreements (with Arab countries, Turkey and the European Union) and monitoring the extent to which Syria is benefitting. Then, we analyze the Syrian foreign trade through foreign trade indicators to get to provide a picture of the economic importance of foreign trade in the period observed, and then to conclude to a number of recommendations and proposals.